THE INFLUENCE OF CUSTOMER EXPERIENCE ON INTEREST USING THE TIX.ID APPLICATION IN PURCHASING CINEMA TICKETS IN JAMBI CITY WITH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE - Ahmad Subhi; Erida Erida; Yenny Yuniarti (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2023)
The perpetrator's business can use the internet and digital marketing as a medium for support activities marketing , like For do promotion, buying and selling process. One of them is the emergence of online sites and applications internet-based _ used to help do activity sales or purchase products online. Study This is study descriptive quantitative aim _ To explain the influence Customer Experience and Customer Satisfaction as well as interest_use repeat consumers who have application Tix. Id . Population in research This is user application Tix.Id in Jambi City with sample as many as 75 respondents . Withdrawal sample use non-probability sampling with the technique purposive sampling . Data collection using google form. Deep data analysis techniques study This is Partial Least Square use application SmartPLS . Research results This show that : Customer Experience and Customer Satisfaction influential positive and significant to Interest Use Repeat , Customer Experience influential positive and significant to Customer Satisfaction. CustomerExperience influence interest use repeat through customer satisfaction as intervening variable